2002
DOI: 10.1080/10258140290018711
|View full text |Cite
|
Sign up to set email alerts
|

Copper/Zinc Superoxide Dismutases in Dictyostelium discoideum : Amino Acid Sequences and Expression Kinetics

Abstract: Genes for Copper/Zinc superoxide dismutases, designated sodA and sodB, in the cellular slime mold Dictyostelium discoideum were analyzed. It was found that these gene products contain charged amino acid residues and hydrophobic stretches in their N-terminal regions, suggesting that they are extracellular Cu/Zn superoxide dismutases. The sodA and sodB are expressed in cells in the growth phase and throughout the developmental phases, suggesting that they are the housekeeping genes. The sodA is induced by H(2)O(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They are expressed during both mitotic growth and multicellular development. One study showed that sodA was induced by H2O2 but not UV, while sodB was induced by both H2O2 and UV (Tsuji et al, 2002). In contrast another study showed that sodA was not induced by either H2O2 or UV (Garcia et al, 2000).…”
Section: Antioxidant Defense Mechanisms In D Discoideummentioning
confidence: 99%
See 2 more Smart Citations
“…They are expressed during both mitotic growth and multicellular development. One study showed that sodA was induced by H2O2 but not UV, while sodB was induced by both H2O2 and UV (Tsuji et al, 2002). In contrast another study showed that sodA was not induced by either H2O2 or UV (Garcia et al, 2000).…”
Section: Antioxidant Defense Mechanisms In D Discoideummentioning
confidence: 99%
“…SOD in D. discoideum. D. discoideum encodes and expresses a number of SODs (Akaza et al, 2002;Garcia et al, 2000;Tsuji et al, 2002) corresponding to the SODs found in humans (Table 1.1).…”
Section: Antioxidant Defense Mechanisms In D Discoideummentioning
confidence: 99%
See 1 more Smart Citation